Determinants of interest ratein emerging marketsA study of banking financial institutionsin Uganda - Tumwine, Sulait; Sejjaaka, Samuel; Bbaale, Edward; Kamukama, Nixon (Emerald Publishing Limited., 2018)
The purpose of this paper is to investigate the determinants of interest rate in emerging markets,focusing on banking financial institutions in Uganda.Using the net interest margin model, interest rate was estimated by applying a panel random effects regression method on 24 banks, while controlling for bank-specific factors,industry and macroeconomic indicators. Data were drawn from annual reports provided by Bank of Uganda Depository Corporation survey from 2008 to 2016.The results indicate that liquidity, equity capital, market power and reserve requirement have a positive effect on interest rate. The study further finds that operational efficiency, lending out ratio,concentration, public sector borrowing and private sector credit have a negative effect on interest rate.However, credit risk does not influence interest rate.Research limitations/implications–Studied banks are grouped in one panel data set; future studies would focus on the differences in banks and establish how these differences affect interest rate. Future study would also focus on how the determinants of interest rate in Uganda are compared with those of other banks in other emerging market countries.Bank managers need to take interest in equity mobilization because it is a reliable and cheaper source of funding bank operations. Banks should emphasize efficient operations to reduce on the cost of doing business. Government should utilize funds borrowed from banks in efficient ways to improve economic growth. The central bank should minimize the use of reserve requirement as a means of controlling money in circulation.This is the first paper that uses annual report data from several banks and periods to investigate the determinants of interest rate in an emerging country.
Determinants of interest rate in emerging markets.
Keywords: Interest rate, Macroeconomic indicators, Bank-specific factors, Industry-level factors